Potensi energi terbarukan pengganti bahan bakar fosil - Sari, Aprilina Eka (Maliki Interdisciplinary Journal, 2024)
The global energy supply will be threatened in the future, the potential for renewal of alternative fuels to replace fossils is still being developed by scientists, after making various efforts there are several potentials that can replace the role of fossils as fuels that have been used by mankind, namely biomass, biofuel, and waste. The basis of this paper is qualitative research. This research uses library research, meaning secondary or indirect data sources are used to collect the sources. Secondary data sources are sources of information that are collected indirectly and utilized. The research includes secondary sources from books, journals, and other research, and the research problem is highlighted on the website. Excessive use of fossil fuels and the emission of greenhouse gases into the atmosphere, which is causing the melting of the polar ice caps and causing unpredictable climate changes and rising air temperatures, according to scientists as well as several natural disasters. several renewable alternative energies that can be used such as biomass, biofuel, and types of industrial waste. Through converting waste into a valuable energy source, increasing the use of biomass from waste can reduce global pollution levels. Apart from being less harmful to the environment than the use of fossil fuels, burning biomass, biofuels, industrial waste can contribute to reducing overall greenhouse gas emissions.